Safeguarding Reimagined: Centering Athletes’ Rights and Repositioning Para Sport to Chart a New Path - Tuakli-Wosornu, Yetsa A.; Kirby, Sandra L. (Frontiers in Psychology, 2022)
Objectives Para sport has much to teach the broader sports world about safeguarding and athlete protections. By centering athletes’ human rights and underlining the rights-based philosophical underpinnings of the Paralympic Movement, we outline how sport can be safer to all players, coaches, and other participants. Methods We address global Human Rights conventions and their application to Para and non-disabled sport. Safe Sport is positioned as a matter of human rights. The nature of interpersonal violence that human beings experience within and outside sport is discussed. The intersectionality of vulnerable identities (related to gender, sexuality, disability, ethnicity, etc.) is reviewed in some detail. Results Rights violations in Para and non-disabled sport illustrate both individual and organizational vulnerabilities. Individual- and organizational-level drivers of abuse, as well as various modes and types of abuse observed in Para sport, are relevant in all sport settings and should be centered in global sport safeguarding work. The rights-based core of Para and similar sports movements, exemplifies this. Conclusion From a Para-informed vantage point, we issue a call to action, where interpersonal violence in sport is reduced by leveraging relevant elements of the Paralympic Movement. This call asks all sport participants to reject a purely capitalist approach to sport and follow a Para sport paradigm; which embodies human achievement (including sporting success), reflects human rights and inherent human dignity, and requires a higher standard of behaviour.